Cytosolic GABA inhibits anion transport by wheat ALMT1. Issue 2 (3rd November 2019) - Long, Yu; Tyerman, Stephen D.; Gilliham, Matthew
Summary: Anion transport by aluminium‐activated malate transporter (ALMT) proteins is negatively regulated by gamma‐aminobutyric acid (GABA), which increases in concentration during stress. Here, the interaction between GABA and wheat ( Triticum aestivum, Ta) TaALMT1 heterologously‐expressed in Xenopus laevis oocytes was investigated. GABA inhibited anion transport by TaALMT1 in membrane patches from the cytosolic, not extracellular membrane face, via a reduction in open probability (NPopen ), not an inhibition of channel current magnitude. TaALMT1 currents in patches frequently exhibited rundown with complete removal of cytosolic factors, but were partially sustained by protein kinase C dependent phosphorylation. When applied to whole oocytes a GABA‐analogue‐BODIPY conjugate inhibited TaALMT1 anion currents from the cytoplasmic face only, whereas free GABA inhibited from both the inside and outside consistent with GABA traversing the TaALMT1 pore then acting from the inside. We propose GABA does not competitively inhibit ALMT conductance through the same pore but rather leads to an allosteric effect, reducing anion channel opening frequency. Across plants GABA is a conserved regulator of anion transport via ALMTs – a family with numerous physiological roles beyond Al 3+ tolerance. Our data suggests that a GABA–ALMT interaction from the cytosolic face has the potential to form part of a novel plant signalling pathway.